Well-being among parents of youth with multiple sclerosis: a preliminary longitudinal study - Hamama, Liat; Hamama-Raz, Yaira; Lebowitz-Sokolover, Keshet; Ganelin-Cohen, Esther (Frontiers in Psychology, 2024)
In 2021, the annual rate of pediatric-onset multiple sclerosis (POMS) in Israel among children was 1.5%, and 4.5% among youth aged 14-18, out of a total of 5,000 multiple sclerosis cases nationwide. Children diagnosed with POMS often display various deficiencies across psychological, cognitive, sensory, and physical areas. As such, POMS poses significant challenges for parents' well-being, with heightened emotional, financial, and physical strains linked to both the immediate and long-term care requirements of their children. In this preliminary study, we examined changes over three time-points in two measures of well-being:satisfaction with life and psychological distress. In addition, the role of perceived social support (PSS) and coping flexibility was examined through a multilevel causal mediation model which suggested that PSS one month post-diagnosis would predict coping flexibility at six months post-diagnosis, which in turn would predict parents' life satisfaction and psychological distress at 12 months post-diagnosis.The research was conducted at a tertiary university-affiliated children's hospital in central Israel. Preliminary data were obtained from 36 parents at three times-points. Participants provided demographic information and filled out the following standardized self-report questionnaires: the Diener's Satisfaction with Life Scale, Kessler's inventory for measuring psychological distress (K6), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Perceived Ability to Cope with Trauma Scale (PACT) for measuring coping flexibility. Results:Over time (12 months), parents reported stable levels of PSS, coping flexibility, satisfaction with life, and psychological distress. In addition, mothers reported significantly greater PSS from friends than did fathers. Regarding the causal mediation model, greater PSS from friends at T1 was significantly associated with an increase in coping flexibility from T1 Parents of Youth with Multiple Sclerosis 2 to T2. In turn, an increase in coping flexibility was associated with a decrease in psychological distress from T1 to T3 (after controlling for PSS).Yet the causal mediation path via coping flexibility to satisfaction with life was not significant. This preliminary study emphasizes the important role of both PSS and coping flexibility for the well-being of parents whose children are affected by POMS, a subject that merits heightened consideration among healthcare professionals dealing with long-term chronic diseases.